Translation, Adaptation, Inscription: Displacing God in Austen’s Sense and Sensibility - Wolf, Alan (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Focusing on a comparative analysis of film adaptations and French translations of Jane Austen’s Sense and Sensibility, this article examines the ideological reconstruction of source texts. More precisely, it proposes a way of describing the inscription and displacement of values in Sense and Sensibility based on a reading of the work in the context of Anglican neoclassical theology. This will provide the basis for the claim that the Anglican via media is displaced whilst allowing us further to explore the relationship between adaptation and translation.